DISTANCE LEARNING METHODS IN ENGLISH AND THEIR EFFECTIVENESS - Tuychieva, Shakhzoda (Журнал иностранных языков и лингвистики, 2022)
This article is about modern technologies in learning and teaching English appropriate use and self-research of the teacher, feeling of responsibility, about bringing news to the lessons, making the lesson interesting and lively written.